Effectiveness of Snakehead Fish Extract on the Healing Time of Perineal Wounds in Postpartum Women Who Experience Perineal Rupture in the Jakarta-Tangerang Region in 2024 - Melisa Putri Rahmadhena; Gibraltar Jala Amazona; Nur Mutmainah; Ridha Niladitya; Fitriana; Wulandari (Postgraduate, University of Mataram, 2024)
Snakehead fish is rich in nutrients, particularly protein and albumin, which are vital for health. Albumin plays a crucial role in the body by aiding the formation of new cell tissue. Without sufficient albumin, cells struggle to regenerate, leading to rapid cell death and hindered development. A study was conducted in the Jakarta-Tangerang area in 2024 to assess the effectiveness of snakehead fish extract on the healing time of perineal wounds in postpartum women with perineal rupture. The study recruited 88 respondents, divided equally into intervention and control groups. Using G-Power Version 3.1.9.4 software, the sample size was determined, and data analysis was performed using independent sample t-tests for normally distributed data and the Mann-Whitney test for non-normally distributed data. Results showed that the intervention group had a significantly shorter average healing time (24.01 days) compared to the control group (64.99 days), with a p-value of 0.000, indicating the effectiveness of snakehead fish extract in accelerating perineal wound healing. The study suggests educating women on the benefits of consuming snakehead fish extract to promote faster recovery from perineal wounds.